Kontroversi Praktik Tahlilan di Masyarakat : Analisis Perspektif Hukum Islam dan Hukum Adat - Naqsa Fazrul Rahman; Hijrah Maulana Ibrahim (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The practice of tahlilan is a religious tradition deeply rooted in the lives of Indonesian Muslim communities as a result of the acculturation between local culture and Islamic teachings. This tradition not only possesses a spiritual dimension in the form of prayers and remembrance for the deceased but also embodies social values such as solidarity, mutual cooperation, and strengthening social relationships within the community. However, the existence of tahlilan has sparked controversy, particularly from the perspectives of Islamic Law and Customary Law. This study aims to analyze the practice of tahlilan from both perspectives and to identify solutions to the dynamics developing within society. The research employs a qualitative method with a sociological approach and descriptive-analytical techniques. The findings indicate that, from the perspective of Islamic Law, tahlilan is viewed differently among Islamic scholars. Some consider it part of ‘urf shahih and bid’ah hasanah because it contains elements of prayer, remembrance, and charity, while others reject it due to the absence of direct precedent from the practices of the Prophet Muhammad SAW and his companions. Meanwhile, from the perspective of Customary Law, tahlilan is regarded as a tradition with significant social functions in maintaining harmony and solidarity within society. The proposed solution is a moderation (wasathiyah) approach that balances cultural preservation with the purity of Islamic teachings while avoiding practices that contradict Islamic law. Therefore, tahlilan can be understood as a flexible socio-religious tradition that remains relevant as long as it does not contain elements of polytheism or impose burdens on the community.